2007
DOI: 10.1055/s-2007-965417
|View full text |Cite
|
Sign up to set email alerts
|

Is Neonatal Circumcision Judicious?

Abstract: From our study, circumcision at 5 months results in significantly fewer serious complications than circumcision in the neonatal period, irrespective of the method used. Therefore, neonatal circumcision should not be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…201,202,[222][223][224][225][226][227][228] Comparison A study with fair evidence evaluated the use of the Gomco versus the Plastibell device in 350 newborn infants. 229 The incidence of infection was higher with the Gomco clamp (2%) versus a lower complication rate (1.3%) with the Plastibell device. Adhesions were also more common with the Gomco clamp, at a rate of 20% vs 6.6% for the Plastibell device.…”
Section: Mogen Clampmentioning
confidence: 88%
“…201,202,[222][223][224][225][226][227][228] Comparison A study with fair evidence evaluated the use of the Gomco versus the Plastibell device in 350 newborn infants. 229 The incidence of infection was higher with the Gomco clamp (2%) versus a lower complication rate (1.3%) with the Plastibell device. Adhesions were also more common with the Gomco clamp, at a rate of 20% vs 6.6% for the Plastibell device.…”
Section: Mogen Clampmentioning
confidence: 88%
“…Machmouchi and Alkhotani compared the outcome of circumcisions conducted in early neonatal period and at 5 months age. Complications including meatal deformities, meatal stenosis, adhesions and infection were more frequent and more significant in the neonatal circumcision group (6). Van Howe found that neonatal circumcision increases the risk of penile inflammation particularly in boys younger than three years old (19).…”
Section: Discussionmentioning
confidence: 95%
“…Complication rates depend on various factors such as anatomic abnormalities, medical comorbidities, surgical techniques, and the age of circumcision (5). Numerous studies have been published concerning post-circumcision meatal stenosis in different ages with inconsistent results (2,(6)(7)(8). In addition, studies regarding the role of circumcision methods in meatal stenosis are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported in the literature that neonatal circumcision is less painful and is associated with fewer complications, but it requires more experience on the part of the surgeon. However, there are reports of increasing surgical complications associated with neonatal circumcision ( 19 - 21 ). The youngest child in our series was 1 month old, while the oldest patient was 14 years old; thus, no neonatal circumcision was performed.…”
Section: Discussionmentioning
confidence: 99%